DISCRIMINANT FUNCTION ANALYSIS TO DISTINGUISH THE PERFORMANCE OF INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) COMPANIES (A STUDY OF U.S. COMPANIES LISTED IN U.S. STOCK MARKET) - Sukma Kinanthi, Enggar
Digitalization has made people alter their needs and ways of life because of numerous comforts and accessibilities through the digital platform and mobile applications. Not only that, digitalization also has significant impact on business entities and even economic conditions. Information and communication technology (ICT) companies are one of the important key aspects of digital economy (UNCTAD, 2019). Many institutions and researchers have conducted the studies to measure the value creation created by digitalization (OECD, 2014; CGMA, 2015; UNCTAD, 2019). However, not many of them emphasize the importance of financial information as a performance measurement of ICT companies that are useful for their sustainability in the midst of the rapid pace of technology. Therefore, this study aims to find the importance of financial information, in this case financial ratios, in assessing the performance of ICT companies. This study uses discriminant function analysis to find the best financial ratios that consistently differentiate ICT companies’ performance based on their grade from credit rating. This scope of this study is 70 US-based companies listed in the US stock market within ICT groups with 35 companies in each group of Investment Grade and Non-investment Grade based on the ratings. Among 23 financial ratios used as original variables (predictor variables), there are 4 financial ratios that best discriminate the performance between the two groups which are ROA, CFO to current liabilities, total debt to EBITDA, and CFO to net sales. This model has a predictive accuracy or early warning ability of 87,1% in the latest full-year financial statements prior to rating date and decrease to 80,0% in the longer period (up to 3rd last full-year financial statements prior to rating date). Since this study sampled the ICT companies in the US, the model drawn from this study reflects the success of US top-rated ICT companies in creating and maintaining superior financial performance. In addition, this model also proofs that financial ratio still has the ability to assess the ICT company’s performance in the current digital era.